2015
DOI: 10.1080/00268976.2014.1000991
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and heats of formation of CXI (X = Br, Cl, F) iodocarbenes: quantum chemical characterisation of the (1 A′), ã(3 A″) and Ã(1 A″) states

Abstract: The equilibrium energies of the iodocarbenes CXI (X = Br, Cl, F) in theirX( 1 A ),ã( 3 A ) andÃ( 1 A ) states and their atomisation and dissociation energies in the complete basis limit were determined by extrapolating valence correlated (R/U)CCSD(T) and Davidson corrected multi-reference configuration interaction (MRCI) energies calculated with the augcc-pVxZ (x = T,Q,5) basis sets and the ECP28MDF pseudopotential of iodine plus corrections for core and core-valence correlation, scalar relativity, spin-orbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…A similar approach to Feller et al, but with smaller basis sets and a simpler extrapolation technique, was used by Bacskay in studies of iodine and bromine containing carbenes. The spin-orbit coupling corrections to the molecular energies, regarded as critical in these systems, were computed by a pseudopotential technique, whereby the Breit–Pauli spin-orbit operator is approximated by an effective one-electron Fock operator in a basis of selected CASSCF or MRCI states.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach to Feller et al, but with smaller basis sets and a simpler extrapolation technique, was used by Bacskay in studies of iodine and bromine containing carbenes. The spin-orbit coupling corrections to the molecular energies, regarded as critical in these systems, were computed by a pseudopotential technique, whereby the Breit–Pauli spin-orbit operator is approximated by an effective one-electron Fock operator in a basis of selected CASSCF or MRCI states.…”
Section: Introductionmentioning
confidence: 99%
“…Based on C 2 F 3 I dissociation limits determined in previous VMI experiments [28], available dissociation limit/thermochemistry data [29][30][31], and the vibrational constants reported in the literature [31][32][33][34][35][36][37][38], the energetic fragmentation thresholds of C 2 F 3 I can be estimated. Of note here are the thresholds for C 2 F 3 + I( 2 P 3/2 ) (3.20±0.05 eV), CF 2 +CFI (4.6±0.1 eV), and CF 2 + CF + I( 2 P 3/2 ) (6.6±0.1 eV) production; all of which are accessible following single-photon excitation at 7.71 eV and potential signatures of which are observed in the data shown in Figs.…”
Section: Spectroscopy and Dynamicsmentioning
confidence: 99%
“…Dissociation resulting in a loss of Br is particularly relevant to atmospheric ozone chemistry as the Br atom is much more destructive to ozone than the other halogen atoms including the Cl atom. Bromine-containing halocarbons especially these bromine-substituted carbenes are the important subject of the experimental and theoretical studies in recent decades. Herein, we focus on CBr 2 carbene.…”
Section: Introductionmentioning
confidence: 99%
“…As the special nature of the lowest singlet state and triplet state have been reported, information on the ground singlet state, the lowest triplet state, and energy separation between them is essential in understanding the chemistry of these halocarbons. Experimental , and theoretical investigations on the lowest three states and energy gaps between them (the à ← X̃ state adiabatic transition energy ( T 00 ) and the ã ← X̃ state adiabatic transition energy (S–T gap)) have been carried out in the past decades. However, the T 00 of CBr 2 are controversial as different groups have indicated that the T 00 are 14962 cm –1 , 14885 cm –1 , 15092 cm –1 , and 15278 cm –1 , by analysis of the laser-induced fluorescence spectra in the latest decades.…”
Section: Introductionmentioning
confidence: 99%